Dexmedetomidine as a Rapid Bolus for Treatment and Prophylactic Prevention of Emergence Agitation in Anesthetized Children. (November 2015) - Hauber, John A.; Davis, Peter J.; Bendel, Laima P.; Martyn, Slava V.; McCarthy, Denise L.; Evans, Minh-Chau; Cladis, Franklyn P.; Cunningham, Sarah; Lang, Robert Scott; Campbell, Neal F.; Tuchman, Jay B.; Young, Michael C.
Abstract : BACKGROUND: Administration of dexmedetomidine (DEX) in the pediatric population for its sedative, analgesic, and anxiolytic properties has been widely reported, despite there being no label indication approved by the U.S. Food and Drug Administration for pediatric patients. Infusions of DEX, rather than bolus administration, are recommended to attenuate the hemodynamic response caused by the α2 -adrenoreceptor agonist. In this prospective, double-blind, randomized study, we examined the effect of rapid IV bolus injection of DEX on emergence agitation and the hemodynamic response in a large sample of children undergoing tonsillectomy with or without adenoidectomy, with or without myringotomy, and/or tympanostomy tube insertion. METHODS: Four hundred patients, aged 4 to 10 years, undergoing tonsillectomy with or without adenoidectomy, with or without myringotomy, and/or tympanostomy tube insertion, were randomized at a 1:1 ratio into 1 of the 2 treatment groups in a double-blinded fashion. After a standardized anesthetic regimen and approximately 5 minutes before the end of surgery, patients in group DEX were administered a rapid IV bolus of 4 μg·mL −1 DEX at a dose of 0.5 μg·kg −1, whereas patients in group saline received a rapid IV bolus of equivalent volume saline. Baseline measurements of heart rate, systolic blood pressure, diastolic blood pressure, respiratory rate, and blood oxygen saturation were collected immediately before study drug administration and every minute thereafter for 5 minutes. In the postanesthesia care unit, vital signs were measured, emergence agitation (EA) was assessed using the Pediatric Anesthesia Emergence Delirium scale, and postoperative opioid use and complications were recorded. RESULTS: The incidence of EA in group DEX was significantly lower than that in group saline, regardless of whether EA was defined as a Pediatric Anesthesia Emergence Delirium score >10 (36% vs 66%, respectively; P < 0.0001; relative risk [95% confidence interval] = 0.527 [0.421–0.660]; number needed to treat = 3.33) or >12 (30% vs 61%, respectively; P < 0.0001; relative risk [95% confidence interval] = 0.560 [0.458–0.684]; number needed to treat = 3.23). Both groups exhibited similar baseline vital signs before study drug injection (all P ≥ 0.602). After injection, group DEX experienced a significant decrease in heart rate for all time points in comparison with group saline (all P < 0.0001). A significant, biphasic blood pressure response was observed in group DEX, specifically, a transient increase in systolic blood pressure at 1 minute after injection ( P < 0.0001) and a subsequent decrease below baseline for 3, 4, and 5 minutes (all P < 0.0001). No patients required treatment for bradycardia, hypertension, or hypotension. A significantly smaller percentage of patients in group DEX received postoperative, supplemental opioid medication compared with group saline (48% vs 73%, respectively; P < 0.0001). Group DEX appeared to experience fewer adverse events than group saline as well (9% vs 17%, respectively; P = 0.025). CONCLUSIONS: Rapid IV bolus administration of DEX in children improved their recovery profile by reducing the incidence of EA. A statistically significant change in hemodynamics was observed, but no patients required any intervention for hemodynamic changes. Furthermore, DEX reduced the incidence of postoperative opioid administration, and a trend of fewer adverse events was observed in group DEX. Abstract : Published ahead of print September 1, 2015